Composite window layer structure for copper-indium-gallium-selenium bottom battery and preparation method of composite window layer structure

By using a composite window layer structure composed of composite oxide layer, ultra-thin metal layer and indium zirconium oxide layer in CIGS bottom battery, the parasitic absorption problem of window layer in the near infrared region in the prior art is solved, and efficient The near-infrared transmission and conductivity increase, which improves the conversion efficiency of CIGS bottom battery and reduces production costs.

CN119497457APending Publication Date: 2025-02-21CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411557764.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing CIGS window layer material has a high parasitic absorption in the near infrared region, resulting in a decrease in its transmittance in the near infrared band, affecting the conversion efficiency of the CIGS bottom battery.

Method used

Using a composite window layer structure composed of a composite oxide layer, an ultra-thin metal layer and an indium zirconium oxide layer, MgZnO, Zn seed layer, Cu film and Zr-doped In2O3 are deposited by co-sputtering method and low-temperature lossless radio frequency sputtering method. The film forms a window layer with uniform film layer, low resistivity and high near infrared transmittance.

Benefits of technology

It effectively improves the overall conductivity of the window layer and the absorption rate of the near-infrared band, improves the conversion efficiency of the CIGS bottom battery, and reduces the thickness of the window layer and reduces the production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497457A_ABST
    Figure CN119497457A_ABST
Patent Text Reader

Abstract

The invention discloses a composite window layer structure for a copper-indium-gallium-selenium bottom battery and a preparation method of the composite window layer structure, and relates to the technical field of thin-film solar batteries. The composite window layer structure is composed of a composite oxide layer, an ultrathin metal layer and an indium zirconium oxide layer. According to the invention, the composite oxide barrier layer / ultrathin metal layer / indium zirconium oxide is used as the window layer, so that the near-infrared light transmittance is enhanced, and the thickness of the original window layer is greatly reduced. According to the invention, the efficiency of the bottom cell is improved, so that the preparation of the high-efficiency laminated cell is realized; the production cost can be effectively reduced, the technological process is simple, and an existing production line is easy to upgrade and reconstruct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thin-film solar cells, and in particular to a composite window layer structure for a copper indium gallium selenide bottom cell and a preparation method thereof. Background Art

[0002] As an important renewable energy source, solar energy has developed rapidly in recent years. Among various commercialized solar cells, copper indium gallium selenide (hereinafter referred to as "CIGS") thin-film solar cells have a tendency to be widely used in photovoltaic building integration, rooftop power generation, mobile energy and other fields due to their good weak light effect, low temperature coefficient and low attenuation efficiency. In addition, the adjustable band gap width and excellent stability have also made CIGS cells as bottom cells in the field of stacked cells attract more and more attention.

[0003] However, the CIGS window layer prepared in actual production is an intrinsic zinc oxide (i-ZnO) layer and a zinc oxide doped with aluminum (AZO) layer. In order to reduce the leakage current of the battery and reduce its series resistance, the thickness is mostly more than 1.2μm, so the cost is relatively high. In addition, the existing window layer materials have certain parasitic absorption in the near-infrared region, which reduces its transmittance in the near-infrared band, thereby affecting the conversion efficiency of the CIGS bottom cell, and ultimately leading to a decrease in the overall efficiency of the stacked cell. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a composite window layer structure for a copper indium gallium selenide bottom cell and a preparation method thereof, which can prepare a composite window layer for a copper indium gallium selenide bottom cell with uniform film layer, low resistivity and high near-infrared transmittance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A composite window layer structure for a copper indium gallium selenide bottom cell, consisting of a composite oxide layer, an ultra-thin metal layer and an indium zirconium oxide layer;

[0007] Wherein, the composite oxide layer serves as a barrier layer, and the ultra-thin metal layer and the indium zirconium oxide layer serve as a composite window layer;

[0008] The composite oxide layer is a MgZnO film with a thickness of 30 to 50 nm, the ultra-thin metal layer is a Zn seed layer with a thickness of 1 to 3 nm and a metal Cu film with a thickness of 7 to 9 nm, and the indium zirconium oxide layer is a Zr-doped In2O3 film with a thickness of 100 to 150 nm.

[0009] Furthermore, the mass ratio of Zr doped in the Zr-doped In2O3 film is 1% to 5%.

[0010] A method for preparing a composite window layer for a copper indium gallium selenide bottom cell comprises the following steps:

[0011] (1) A MgZnO film is first deposited on the buffer layer of the copper indium gallium selenide bottom cell by a co-sputtering method to form a barrier layer, and then a Zn seed layer and a metal Cu film are sequentially deposited on the barrier layer by a DC sputtering method to form an ultra-thin metal layer;

[0012] (2) A Zr-doped In2O3 film is deposited on an ultra-thin metal layer using a low-temperature, non-destructive radio frequency sputtering method, and a high-performance composite window layer is obtained after annealing.

[0013] Furthermore, the process parameters of the co-sputtering method in step (1) are: sputtering power of 50-150 W, working gas pressure of 0.1-1.5 Pa, argon flow rate of 30 ppm, oxygen flow rate of 3 ppm, Zn target sputtering time of 10-15 min, and Mg target sputtering time of 1-5 min.

[0014] Furthermore, the process parameters of the DC sputtering method in step (1) are: sputtering power of 20-50 W, working gas pressure of 0.1-1 Pa, argon gas flow rate of 30 ppm, Zn target sputtering time of 1 s, and Cu target sputtering time of 10 s.

[0015] Furthermore, the process parameters of the low-temperature non-destructive RF sputtering method in step (2) are: sputtering power of 40 to 60 W, working gas pressure of 0.1 to 2 Pa, argon gas flow rate of 30 ppm, and sputtering time of 90 to 140 min; the annealing process parameters in step (2) are: annealing temperature of 80 to 120 ° C, and annealing time of 30 to 60 min.

[0016] The present invention can effectively reduce the leakage current of the battery and improve the shunt resistance by introducing MgZnO as a barrier layer. The ultra-thin metal layer combining the Zn seed layer and the Cu film can improve the uniformity and continuity of the Cu film. The Zr-doped In2O3 film can reduce the parasitic absorption of the window layer in the near-infrared region and improve the average transmittance in the near-infrared region. The combination of the ultra-thin metal layer can further improve the overall conductivity of the window layer.

[0017] Beneficial effects of the present invention:

[0018] The composite window layer for the copper indium gallium selenide bottom cell prepared by this method can not only effectively improve its overall conductivity, but also increase the absorption of the bottom cell in the near-infrared band, thereby improving the conversion efficiency of the bottom cell. In addition, the thickness of the overall window layer is greatly reduced, effectively reducing production costs, and the process flow is simple, making it easy to upgrade and transform existing production lines. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described below in conjunction with the accompanying drawings.

[0020] Figure 1 This is a schematic diagram of the structure of the composite window layer for the copper indium gallium selenide bottom cell of the present invention;

[0021] Figure 2 This is a visible near-infrared transmittance diagram of the composite window layer for the copper indium gallium selenide bottom cell prepared in Example 1 of the present invention;

[0022] Figure 3 This is a SEM cross-sectional view of the composite window layer for the copper indium gallium selenide bottom cell prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] like Figure 1 As shown, the present invention provides a composite window layer structure for a copper indium gallium selenide bottom cell, comprising a composite oxide layer 1, an ultra-thin metal layer 2 and an indium zirconium oxide layer 3, wherein the ultra-thin metal layer 2 comprises a Zn seed layer 4 and a metal Cu film 5.

[0025] Embodiment 1

[0026] The method for preparing a composite window layer for a copper indium gallium selenide bottom cell comprises the following steps:

[0027] (1) A MgZnO film was first deposited on the buffer layer of the copper indium gallium selenide bottom cell by co-sputtering. Metal Mg and Zn targets were selected. A DC power supply was used. The sputtering powers were 50W and 150W respectively. The working pressure was 0.1Pa. The argon flow rate was 30ppm. The oxygen flow rate was 3ppm. The Zn target sputtering time was 15min. The Mg target was turned on in the middle. The sputtering time was 5min. A 50nm MgZnO film was obtained. A Zn seed layer was first deposited on the surface of the MgZnO film by DC sputtering. A metal Zn target was selected. The sputtering power was 20W. The working pressure was 0.1Pa. The argon flow rate was 30ppm. The sputtering time was 1s. A 1nm thick Zn seed layer was obtained. Then a metal Cu film was deposited. A metal Cu target was selected. The sputtering power was 50W. The working pressure was 0.1Pa. The argon flow rate was 30ppm. The sputtering time was 10s. A 9nm thick Cu film was obtained.

[0028] (2) A low-temperature non-destructive radio frequency sputtering method was used to deposit a Zr-doped In2O3 film on the ultra-thin metal layer. An In2O3 ceramic target with a Zr-doped mass ratio of 1% was selected, the sputtering power was 40 W, the working gas pressure was 0.1 Pa, the argon gas flow rate was 30 ppm, the sputtering time was 90 min, and after cooling to room temperature, the in-situ annealing temperature was 80 ° C, the annealing time was 30 min, and an IZrO film with a thickness of 100 nm was obtained.

[0029] Combination Figures 2-3 As shown, the copper indium gallium selenide bottom cell in this embodiment is prepared on a glass substrate with a composite window layer. The obtained sample is tested by a spectrophotometer, and the average transmittance in the visible and near-infrared bands is measured to be 80.9%. A four-probe electrical test is performed, and the square resistance is measured to be 12Ω / □.

[0030] Embodiment 2

[0031] The method for preparing a composite window layer for a copper indium gallium selenide bottom cell comprises the following steps:

[0032] (1) A MgZnO film was first deposited on the buffer layer of the copper indium gallium selenide bottom cell by co-sputtering. Metal Mg and Zn targets were selected. A DC power supply was used. The sputtering powers were 60W and 120W respectively. The working pressure was 0.7Pa. The argon flow rate was 30ppm. The oxygen flow rate was 3ppm. The Zn target sputtering time was 12min. The Mg target was turned on in the middle. The sputtering time was 3min. A 40nm MgZnO film was obtained. A Zn seed layer was first deposited on the surface of the MgZnO film by DC sputtering. A metal Zn target was selected. The sputtering power was 35W. The working pressure was 0.5Pa. The argon flow rate was 30ppm. The sputtering time was 1s. A 2nm thick Zn seed layer was obtained. Then a metal Cu film was deposited. A metal Cu target was selected. The sputtering power was 35W. The working pressure was 0.5Pa. The argon flow rate was 30ppm. The sputtering time was 10s. A Cu film with a thickness of 8nm was obtained.

[0033] (2) A low-temperature non-destructive radio frequency sputtering method was used to deposit a Zr-doped In2O3 film on the ultra-thin metal layer. An In2O3 ceramic target with a Zr-doped mass ratio of 3% was selected, the sputtering power was 50 W, the working gas pressure was 1 Pa, the argon gas flow rate was 30 ppm, the sputtering time was 100 min, and after cooling to room temperature, the in-situ annealing temperature was 100 ° C, the annealing time was 45 min, and an IZrO film with a thickness of 120 nm was obtained.

[0034] The copper indium gallium selenide bottom cell in this embodiment was prepared on a glass substrate with a composite window layer. The obtained sample was tested by a spectrophotometer, and the average transmittance in the visible and near-infrared bands was measured to be 80.5%. The sample was subjected to a four-probe electrical test, and the square resistance was measured to be 11Ω / □.

[0035] Embodiment 3

[0036] The method for preparing a composite window layer for a copper indium gallium selenide bottom cell comprises the following steps:

[0037] (1) A MgZnO film was first deposited on the buffer layer of the copper indium gallium selenide bottom cell by co-sputtering. Metal Mg and Zn targets were selected. A DC power supply was used. The sputtering powers were 70W and 100W respectively. The working pressure was 1.5Pa. The argon flow rate was 30ppm. The oxygen flow rate was 3ppm. The Zn target sputtering time was 10min. The Mg target was turned on in the middle. The sputtering time was 1min. A 30nm MgZnO film was obtained. A Zn seed layer was first deposited on the surface of the MgZnO film by DC sputtering. A metal Zn target was selected. The sputtering power was 50W. The working pressure was 1Pa. The argon flow rate was 30ppm. The sputtering time was 1s. A 3nm thick Zn seed layer was obtained. Then a metal Cu film was deposited. A metal Cu target was selected. The sputtering power was 20W. The working pressure was 1Pa. The argon flow rate was 30ppm. The sputtering time was 10s. A 7nm thick Cu film was obtained.

[0038] (2) A low-temperature non-destructive radio frequency sputtering method was used to deposit a Zr-doped In2O3 film on the ultra-thin metal layer. An In2O3 ceramic target with a Zr-doped mass ratio of 5% was selected, the sputtering power was 60 W, the working gas pressure was 2 Pa, the argon gas flow rate was 30 ppm, the sputtering time was 140 min, and after cooling to room temperature, the in-situ annealing temperature was 120 ° C, the annealing time was 60 min, and an IZrO film with a thickness of 150 nm was obtained.

[0039] The copper indium gallium selenide bottom cell in this embodiment was prepared on a glass substrate with a composite window layer. The obtained sample was tested by a spectrophotometer, and the average transmittance in the visible and near-infrared bands was measured to be 80.1%. The sample was subjected to a four-probe electrical test, and the square resistance was measured to be 9.8Ω / □.

[0040] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.

Claims

1. A composite window layer structure for a copper indium gallium selenide bottom cell, characterized in that: It is composed of a composite oxide layer, an ultra-thin metal layer and an indium zirconium oxide layer; Wherein, the composite oxide layer serves as a barrier layer, and the ultra-thin metal layer and the indium zirconium oxide layer serve as a composite window layer; The composite oxide layer is a MgZnO film with a thickness of 30 to 50 nm, the ultra-thin metal layer is a Zn seed layer with a thickness of 1 to 3 nm and a metal Cu film with a thickness of 7 to 9 nm, and the indium zirconium oxide layer is a Zr-doped In2O3 film with a thickness of 100 to 150 nm.

2. The composite window layer structure for a copper indium gallium selenide bottom cell according to claim 1, characterized in that: The mass ratio of Zr doped in the Zr-doped In2O3 film is 1% to 5%.

3. The method for preparing a composite window layer structure for a copper indium gallium selenide bottom cell according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) A MgZnO film is first deposited on the buffer layer of the copper indium gallium selenide bottom cell by a co-sputtering method to form a barrier layer, and then a Zn seed layer and a metal Cu film are sequentially deposited on the barrier layer by a DC sputtering method to form an ultra-thin metal layer; (2) A Zr-doped In2O3 film is deposited on an ultra-thin metal layer using a low-temperature, non-destructive radio frequency sputtering method, and a high-performance composite window layer is obtained after annealing.

4. The method for preparing a composite window layer structure for a copper indium gallium selenide bottom cell according to claim 3, characterized in that: The process parameters of the co-sputtering method in step (1) are: sputtering power of 50-150 W, working gas pressure of 0.1-1.5 Pa, argon flow rate of 30 ppm, oxygen flow rate of 3 ppm, Zn target sputtering time of 10-15 min, and Mg target sputtering time of 1-5 min.

5. The method for preparing a composite window layer structure for a copper indium gallium selenide bottom cell according to claim 3, characterized in that: The process parameters of the DC sputtering method in step (1) are: sputtering power of 20-50 W, working gas pressure of 0.1-1 Pa, argon gas flow rate of 30 ppm, Zn target sputtering time of 1 s, and Cu target sputtering time of 10 s.

6. The method for preparing a composite window layer structure for a copper indium gallium selenide bottom cell according to claim 3, characterized in that: The process parameters of the low-temperature non-destructive RF sputtering method in step (2) are: sputtering power of 40 to 60 W, working gas pressure of 0.1 to 2 Pa, argon gas flow rate of 30 ppm, and sputtering time of 90 to 140 min.

7. The method for preparing a composite window layer structure for a copper indium gallium selenide bottom cell according to claim 3, characterized in that: The annealing process parameters in step (2) are: annealing temperature is 80-120° C., and annealing time is 30-60 min.